ANALISIS KUALITAS PELAYANAN DALAM MEMBENTUK LOYALITAS PELANGGAN AYAM POTONG PADA CV PANJI JAYA ABADI CIPUTAT - Dean Syavira Zahro; Ali Mubarok (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the role of service quality in building customer loyalty at CV Panji Jaya Abadi. The study used a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used the Miles and Huberman model. The results showed that fast, friendly, responsive service and timely delivery influenced customer satisfaction and loyalty. In addition, good communication between the company and customers also increased customer trust in CV Panji Jaya Abadi. Based on the SWOT analysis, the company has strengths in service and product quality, but still has weaknesses in promotion and price competition. Thus, service quality has an important role in maintaining customer loyalty at CV Panji Jaya Abadi.